OBSERVATIONS ON THE SPECIES OF DORIPPE FROM THE INDO-MALAYAN REGION - Serene, Raoul; Romimohtarto, Kasijan (Marine Research in Indonesia, 1969)
Among the eight Indo-Pacific species of Dorippe, four inhabiting the Indo-Malayan region were represented in the collection of the National Museum of Singapore. In order to extend our review to all the IndoPacific species, this material was complemented by specimens of three other species, two from Japan, one from Australia. Only one species was not available. The conspicuous differences illustrated by the first male pleopods lead to the partition of Dorippe into five different taxa; two new genera and two new sub-genera are added to Dorippe sensu stricto.